Factors associated with physical activity promotion efforts in individuals with chronic diseases: A systematic review from the perspective of patients. (April 2023) - Hu, Rui; Hui, Stanley Sai-chuen; Lee, Eric Kam-pui; Stoutenberg, Mark; Wong, Samuel Yeung-shan; Yang, Yi-jian
Abstract: Objectives: To determine factors associated with healthcare provider physical activity (PA) promotion in individuals with chronic diseases from the perspective of patients. Methods: A systematic review of literature was conducted between March and April 2022 by searching five databases. Studies were included if they used survey data, published in English or Chinese, and investigated factors influencing healthcare provider PA promotion in chronic diseases from the perspective of adult patients. Retrieved factors were extracted and mapped to Anderson's Behavioral Model of Health Services Use. Quality of each study was assessed using the NIH Quality Assessment Tool. Results: Thirteen articles were included for final analysis. The quality of the included studies ranged from fair to good. A series of factors were positively related to healthcare provider PA promotion (e.g., having emotional support or public programs for PA). Conflicting results were found for other factors (e.g., age and gender). Conclusions: A series of factors may impact the incorporation of PA promotion into clinical care. More studies with well-designed surveys using primary data collection are suggested to confirm these findings. Practice implications: Factors identified from this review provide insights for developing of strategies related to healthcare provider PA promotion for individuals with chronic diseases.